Adaptive and User-Centered HCI for Intelligent Technologies: A Global Perspective - Abdurrohman (Indonesian Scientific Publication, 2024)
Human-Computer Interaction (HCI) within intelligent systems plays a critical role in shaping user experience, particularly through effective design, usability, and accessibility. This narrative review aims to synthesize current research trends and challenges in designing inclusive and adaptive HCI environments. Literature was gathered from Scopus and Google Scholar using keywords such as